Under contract : the invisible workers of America's global war - Coburn, Noah (Stanford University Press, 2018)
"War is one of the most lucrative job markets for an increasingly global workforce. Most of the work on American bases, everything from manning guard towers to cleaning the latrines to more technical engineering and accounting jobs, has been outsourced to private firms that then contract out individual jobs, often to the lowest bidder. An'American' base in Afghanistan or Iraq will be staffed with workers from places like Sri Lanka, Bangladesh, the Philippines, Turkey, Bosnia, and Nepal: so-called 'third-country nationals'. Tens of thousands of these workers are now fixtures on American bases. Yet, in the plethora of records kept by the U.S. government, they are unseen and uncounted--their stories untold. Noah Coburn traces this unseen workforce across seven countries, following the workers'often zigzagging journey to war. He confronts the varied conditions third-country nationals encounter, ranging from near slavery to more mundane forms of exploitation. Visiting a British Imperial training camp in Nepal, U.S. bases in Afghanistan, a café in Tbilisi, offices in Ankara, and human traffickers in Delhi, Coburn seeks out a better understanding of the people who make up this unseen workforce, sharing powerful stories of hope and struggle. Part memoir, part travelogue, and part retelling of the war in Afghanistan through the eyes of workers, Under Contract unspools a complex global web of how modern wars are fought and supported, narrating war stories unlike any other. Coburn's experience forces readers to reckon with the moral questions of a hidden global war-force and the costs being shouldered by foreign nationals in our name."--Publisher description.